CHALLENGES EXPERIENCED IN THE IMPLEMENTATION OF SPECIAL NEEDS EDUCATION POLICY IN KENYA AND THE CURRENT STATUS IN THE COMPETENCE BASED CURRICULUM . - Tarsilla, Kibaara (Advances in Social Sciences Research Journal, 2021)
The Kenya Special Needs Education Policy Framework 2009 provided a legal framework that was relevant and guided the provision of Special Needs Education in Kenya. The implementation of the policy has seen Kenya achieve many milestones including increased enrolment, which rose from 22,000 learners in 1999 to 108,221 in 290 special primary institutions and 2057 Special units/integrated programmes (MOE 2018).